Formulation and evaluation of domperidone pellets prepared by powder layering technology - Kibria, Golam; Akhter, Afsana; Ariful Islam, K M (Asian Journal of Pharmaceutics (AJP), 2014)
The goal of the present study is to evaluate the influence of the formulation and operating conditions on pellet preparation by the pan technique.The effect of initial core weight on the physical parameters of pellets as well as to conduct stability study was also the goal of this study. For this domperidone maleate was selected as the model drug. Pellets were prepared by layering of powdered drug on sugar-based cores. Inert cores were intermittently treated with micronized drug powder and binding solution. This treatment led to the formation of multiple layers of drug particles around an inert core resulting in the production of pellets that can further be coated by different polymers to obtain modified release formulations. Scanning electron microscopy was employed to image the surface morphology of the prepared pellets. Drug loading efficiency, % yield, size, and shape uniformity of pellets were increased along with increasing the initial core weight. Drug content and dissolution study were performed by following HPLC and UV–Visible method. About 50% and 80% drug was released within 7.72 m and 13.66 m respectively in 0.1N HCl media (pH 1.2). Physical appearance of the prepared pellets, potency, moisture content, pellets size and shape, dissolution data, release rate constant, diffusion exponent (P<.05) over the stability period showed that the system is efficient for the production of highly stable formulations. This study also showed the good performance of the conventional coating pan system in obtaining instant release domperidone pellets prepared by the powder layering technique.